1998
DOI: 10.1063/1.122126
|View full text |Cite
|
Sign up to set email alerts
|

Lattice deformation and magnetic properties in epitaxial thin films of Sr1−xBaxRuO3

Abstract: Crystal structure and magnetic properties in epitaxially grown Sr1−xBaxRuO3 on SrTiO3 substrates were determined. Epitaxial Sr1−xBaxRuO3 exhibits a simple perovskite structure in the whole region of the Ba/Sr ratio, in contrast to the complex hexagonal layered perovskite of Ba-rich bulk Sr1−xBaxRuO3, which has plane-sharing oxygen octahedra. Tetragonal deformation was enhanced from pseudocubic in SrRuO3 to a highly distorted tetragonal lattice in BaRuO3. Electronic properties such as conductivity and magnetiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
(10 reference statements)
0
13
2
Order By: Relevance
“…Such elemental intermixing of A and B cations and the formation of oxygen vacancies in SRO undoubtedly have a strong effect on its electrical and magnetic properties. 30,31 For example, Ti doping and oxygen vacancies have been shown to increase the electrical resistance of SRO tenfold. 29,30 An increase in the resistance of the SRO electrode would increase the screening length in an FTJ, forming a passive layer, and resulting in a thicker critical thickness for the ferroelectric BTO layer.…”
Section: Resultsmentioning
confidence: 99%
“…Such elemental intermixing of A and B cations and the formation of oxygen vacancies in SRO undoubtedly have a strong effect on its electrical and magnetic properties. 30,31 For example, Ti doping and oxygen vacancies have been shown to increase the electrical resistance of SRO tenfold. 29,30 An increase in the resistance of the SRO electrode would increase the screening length in an FTJ, forming a passive layer, and resulting in a thicker critical thickness for the ferroelectric BTO layer.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that (205) BRO plane can be epitaxially grown on the (001) STO and (001) LaAlO 3 substrate. [13][14][15]18) In this study, (104) BRO plane was also epitaxially grown on the (001) STO substrate ( Fig. 1(a)).…”
Section: Resultsmentioning
confidence: 99%
“…12) Table 1 summarized that the literature data on the structural and electrical properties for 4H and 9R BRO single crystals and epitaxial BRO thin films. 5,[11][12][13][14][15]19,20) For single crystals, a anisotropical temperature dependence of electrical resistivity between in-plane (ab) and out-of-plane (c) was observed only in 9R BRO. 12) This difference between 4H and 9R BRO might be caused by a variation from stacking sequence of face-sharing octahedra with small Ru-Ru distance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12) Although the relationship between the lattice parameter perpendicular to the surface (c-axis length) and the electrical conductivity of epitaxial BSRO thin films grown on (001) SrTiO 3 substrate has been reported, the effect of Ba substitution in SRO thin film on the microstructure and electrical property of non-constrained BSRO thin film should be studied to realize its practical use as a thin film electrode and conductive paste. BSRO thin films prepared by MOCVD have been found to contain a significant amount of BaCO 3 and metallic Ru, 11) and therefore the Ba substitution effect on the lattice parameter and electrical conductivity of polycrystalline BSRO thin film has not been understood.…”
Section: Introductionmentioning
confidence: 99%